2016
DOI: 10.1016/j.jadohealth.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Weight and Anabolic Steroid Misuse Among US Adolescent Boys

Abstract: Purpose Anabolic steroid misuse is a growing concern among adolescent boys, and chronic misuse is associated with multisystemic health consequences. However, little is known about weight related predictors of anabolic steroid misuse. We examined the prediction of lifetime anabolic steroid misuse as a function of self-perceived weight status among US adolescent boys. Methods Analysis was undertaken using the 2013 Youth Risk Behavior Survey, a nationally representative data set sampling public and private high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
0
18
1
3
Order By: Relevance
“…Bolstering this prior research, we found that males with increased drive for muscularity were four times more likely to use muscle-building products compared to those with lower drive for muscularity, which is in line with previous research suggesting that risk for use of musclebuilding products may be connected to an overall general vulnerability to abuse substances. Only three men reported use of AAS, which is considerably lower than recent findings reporting disturbingly high rates of use of AAS in adolescent male populations (Jampel, Murray, Griffiths, & Blashill, 2016). Although it is difficult to determine why the prevalence is lower in the current study, other studies have found that AAS use is typically less prevalent compared to other forms of muscle-building supplements and drugs (Gahche et al, 2011;Kanayama, Hudson, & Pope Jr., 2010).…”
Section: Discussioncontrasting
confidence: 70%
“…Bolstering this prior research, we found that males with increased drive for muscularity were four times more likely to use muscle-building products compared to those with lower drive for muscularity, which is in line with previous research suggesting that risk for use of musclebuilding products may be connected to an overall general vulnerability to abuse substances. Only three men reported use of AAS, which is considerably lower than recent findings reporting disturbingly high rates of use of AAS in adolescent male populations (Jampel, Murray, Griffiths, & Blashill, 2016). Although it is difficult to determine why the prevalence is lower in the current study, other studies have found that AAS use is typically less prevalent compared to other forms of muscle-building supplements and drugs (Gahche et al, 2011;Kanayama, Hudson, & Pope Jr., 2010).…”
Section: Discussioncontrasting
confidence: 70%
“…Adolescent males who perceive themselves as under-or overweight are nearly 4 times more likely to use anabolic steroids to attempt to change body composition as compared with those who perceive themselves as being at an appropriate weight. 84 The AAP policy statement "Use of Performance-Enhancing Substances" reviews the risks of supplements and drugs used for weight gain in detail; Table 8 provides a summary of performance-enhancing substances and their effects adapted from this statement. 85 …”
Section: Unhealthy Weight Gainmentioning
confidence: 99%
“…For example, Cafri et al (2006) found that a desire for increased muscularity was significantly associated with AAS use among young adult men. Recently, Jampel et al (2016) found that perceiving oneself as either very underweight or very overweight was associated with AAS use, suggesting that males who use AAS may do so to gain muscularity and/or reduce body fat. Relatedly, among men who use AAS, many report decreasing fat to be an important motivation (Ip et al, 2011;Cohen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%